THE IMPLEMENTATION OF ROLE PLAYING METHOD TO IMPROVE STUDENT ACTIVITIES AND SPEAKING SKILLS (Study on Indonesian Subject of Grade IV SD Negeri 11 Kota Bengkulu) - Baniah Barizah; Alexon Alexon (UNIB Press, 2018)
This study aims to improve the activity and speaking skills of students in learning Indonesian in grade IV SD Negeri 11 Bengkulu City. This research is a classroom action research combined with a quasi-experimental. The subjects of this study were fourth grade students of SD Negeri 11 Bengkulu City as the PTK class, the experimental class, and the control class. Data collection techniques in this study used observation sheets and learning achievement tests given to students to get answers from students in the form of oral, written, or action tests. The results of this study indicate that: (1) Role playing method can increase student activity in learning Indonesian in grade IV SD Negeri 11 Bengkulu City; (2) The role playing method can improve speaking skills in Indonesian language learning in Class IV SD Negeri 11 Bengkulu City; (3) Role playing method to improve student activity and student speaking skills in learning Indonesian in grade IV SD Negeri 11 Bengkulu City. Data analysis using the average value, classical learning completeness, and hypothesis testing analysis. The results showed that the teacher's ability to implement the learning method, namely the first cycle score of 25.5 with sufficient category, the second cycle score 37.5 with good category and the third cycle score 42 with good category. In improving students 'speaking activities and skills in learning Indonesian, it is better to use the role playing method because it has been proven to be effective in increasing students' speaking activity and skills